PENGARUH PARTISIPASI ANGGOTA DAN KEMAMPUAN MANAJERIAL PENGURUS TERHADAP KEBERHASILAN USAHA KOPERASI : Studi pada Koperasi Pegawai Republik Indonesia di Kabupaten Bekasi - Febby Aulia Siva, - (2019)
This study aims to determine the effect of cooperative member participation and managerial ability of cooperative managers on the success of cooperative businesses in the Cooperative Employees of the Republic Indonesia in Bekasi. The research method used is an explanatory survey with data collection techniques throught questionnaires. The sampling technique used random sampling with a total sample of 195 members of the Cooperative Employees of the Republic Indonesia in Bekasi. The object of this research is the success of the cooperative business, the participation of cooperative members and managerial ability of cooperative managers. Data management was performed using linear regression analysis model with the help of computer program SPSS Version 24. The result of the research shows: (1) Member participation has an positive effect on the success of cooperative businesses, where member participation can give significant influence in achieving the success of cooperative business. (2) The managerial ability of the management has an positive effect on the success of the cooperative business, where the managerial ability of the management can give significant influence in achieving the success of the cooperative business. (3) Member participation and managerial ability of the management have a positive and significant effect on the success of the cooperative business, where the significance value of count is smaller than the level of significance.